Domestic Tourists' Perceptions of Tourism Facilities at Bali Bird Park - Kadek Cahya Rika Manikaputri; I Wayan Sukma Winarya Prabawa; Ida Bagus Putra Negarayana (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine the perception of tourists towards tourist facilities at Bali Bird Park. This study used a quantitative descriptive method with a sample of 100 respondents who had visited Bali Bird Park with a minimum of 1 visit. The results of this study concluded that the tourist facilities at Bali Bird Park were generally in good condition. However, there are indicators for each variable that have the smallest average, namely: 1) Tourist attractions at Bali Bird Park have a place for tourists to relax while enjoying the attractions provided so that they are more comfortable in their activities, 2) Easy to find accommodation closest to Bali Bird Park, 3) There are clear directions. These three indicators need to be the main concern for managers to improve the quality of tourist facilities at Bali Bird Park so that they can make visiting tourists feel satisfied.